‘Remapping External and Internal Terrains’ in Indigenous Canadian Literature: An Ecocritical Study of Select Canadian fiction (Literary Voice, 2023)
Native environmental literature is often misconstrued as empty praise of everything natural and that aboriginals are an integral part of nature giving them a holistic mode of subsistence. The interconnections between the natural world and the natives have been a part of numerous literatures, especially the ones that give voice to aboriginal expression. Canadian literature has often been caught between the Eurocentric appreciation of nature's beauty and the aboriginal expression of nature's essence. The present article explores various nuances of ecology as reflected in the select Canadian literary texts.
Keywords: Aboriginal literature, ecology, essentialism, eco-hybridity, topographies